2019
DOI: 10.1108/bfj-08-2018-0563
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between food neophobia, domain-specific innovativeness, and food festival revisit intentions

Abstract: Purpose The purpose of this paper is to investigate the influence of two personality traits (i.e. food neophobia (FN) and domain-specific innovativeness (DSI)) on revisit intentions of consumers in the food festival context. Design/methodology/approach The study adopted a FN scale, DSI scale and food festival revisit intention scale to capture the study constructs. Furthermore, data were collected from 265 food festival attendees in the town of Udupi (State of Karnataka, India). Furthermore, the study adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 85 publications
(87 reference statements)
0
20
0
Order By: Relevance
“…Neophobia also affect tourists' motivations to experience local food at a t destination (e.g., Ji et al, 2016;Kim et al, 2009;Mak, Lumbers, Eves, & Chang, 2017;Payini, Ramaprasad, Mallya, Sanil, & Patwardhan, 2019).…”
Section: Neophobia and Tourists' Food Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neophobia also affect tourists' motivations to experience local food at a t destination (e.g., Ji et al, 2016;Kim et al, 2009;Mak, Lumbers, Eves, & Chang, 2017;Payini, Ramaprasad, Mallya, Sanil, & Patwardhan, 2019).…”
Section: Neophobia and Tourists' Food Experiencesmentioning
confidence: 99%
“…For example, Kim et al (2010) suggested that neophilia is one of the most important psychological factors determining local food consumption at a destination. Neophobia also affect tourists' motivations to experience local food at a t destination (e.g., Ji et al, 2016; Kim et al, 2009; Mak, Lumbers, Eves, & Chang, 2017; Payini, Ramaprasad, Mallya, Sanil, & Patwardhan, 2019).…”
Section: Conceptual Development and Hypothesesmentioning
confidence: 99%
“…Craft beer festivals are often considered fun and exciting, and as a result the nature of the event can leave a positive image of the event and destination in the minds of the consumer (Hixson et al, 2011;Lee et al, 2012;Zong and Zhao, 2013;Kim et al, 2017). When consumers have positive experiences at a craft beer festival, the annual festival receives benefits via positive word-of-mouth (WOM) and revisit intention (Payini et al, 2020). Additionally, the destination region or city also reaps the rewards of annual visitors (some repeat visitors) with the new spending from non-locals (tourists) in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the hospitality and tourism operators are applying innovation to improve food production especially during historic events and festivals to enhance revisit intentions (Payini et al, 2019) including other tourism outcomes (Stamboulis and Skayannis, 2003). However, innovation and tourist site revisit is driven by digital tourism experiences.…”
Section: Literature Review Theory and Hypotheses Development Social C...mentioning
confidence: 99%